Evolution of microgrids with converter-interfaced generations: Challenges and opportunities. (July 2019) - Hossain, Md Alamgir; Pota, Hemanshu Roy; Hossain, Md Jahangir; Blaabjerg, Frede
Highlights: Definition of a microgrid is established after analysing well-known definitions. Characteristics of microgrids are summarised. A clear distinction between a distribution network and microgrid is presented. Challenges of a microgrid are briefly discussed, with the direction of future research trend. Abstract: Although microgrids facilitate the increased penetration of distributed generations (DGs) and improve the security of power supplies, they have some issues that need to be better understood and addressed before realising the full potential of microgrids. This paper presents a comprehensive list of challenges and opportunities supported by a literature review on the evolution of converter-based microgrids. The discussion in this paper presented with a view to establishing microgrids as distinct from the existing distribution systems. This is accomplished by, firstly, describing the challenges and benefits of using DG units in a distribution network and then those of microgrid ones. Also, the definitions, classifications and characteristics of microgrids are summarised to provide a sound basis for novice researchers to undertake ongoing research on microgrids.